Genetic Analysis of a Pyocin-Resistant Lipooligosaccharide (LOS) Mutant of Haemophilus ducreyi: Restoration of Full-Length LOS Restores Pyocin Sensitivity - Filiatrault, Melanie J. (American Society for Microbiology, 2001)
DNA sequence and Southern blot analyses were used to determine the genetic defect of a Haemophilus ducreyi pyocin-resistant lipooligosaccharide (LOS) mutant, HD35000R. The region of the HD35000R chromosome containing the suspected mutation was amplified, and sequence analysis detected a 3,189-bp deletion. This deletion resulted in the loss of the entire waaQ gene, another open reading frame that encodes a putative homolog to a hypothetical protein (HI0461) of H. influenzae, the gene encoding an argininosuccinate synthase homolog, and a change in the 3′ sequence of the lgtF gene. Southern blot analysis confirmed that no genomic rearrangements had occurred. Isogenic LOS mutants and the respective complemented mutants were evaluated for susceptibility to pyocin C. The mutants expressing truncated LOS were resistant to lysis by pyocin C, and complementation restored sensitivity to the pyocin. We conclude that HD35000R is defective in both glycosyltransferase genes and that pyocin resistance is due to truncation of the full-length LOS molecule.